Ectoparasites and endoparasites of locally produced laboratory rats - Tuan Kamaluddin, Tuan Ajmal (2015)
Laboratory rats, besides mice, guinea pigs and hamster, are commonly used in Malaysia in research studies. Good quality laboratory rats are categorized as specific-pathogenic-free (SPF) while others that are somewhat of lower quality are categorized as conventional animals. Conventional animals however, do carry pathogenic and potentially pathogenic organisms that can harm both the animals itself and also humans. More importantly the pathogenic organisms can interfere with research in many ways and results obtained from using such animals may not be valid. Therefore, objective of this study is to screen for parasitic infestation in laboratory rats that are produced locally. Five laboratory rats each from three different suppliers were selected randomly and used in this project. The rats were euthanized using CO2 before samples were collected. Samples obtained were urine, faeces and fur as well as internal organs to identify any possible ectoparasites and endoparasites in those animals. From this study, it showed that most of the laboratory rats from the three suppliers do carried both ectoparasites and endoparasites. The parasites found are Ornithonyssus bacoti, Glycyphagus domesticus, Syphacia oblevata, Syphacia muris, and Aspiculuris tetraptera. It is interesting to note that Ornithonyssus bacoti, which is a bird parasite, was also found in the rat. How the parasite managed to be present on the rat is an interesting question. This parasite however, can also infect humans. Many of the parasites found do not seem to affect the health of the rats but some are known to have affected the health of the animals when the parasitic load is heavy especially when the rats undergo stressful conditions such as during an experiment. It can be concluded that the laboratory rats produced by the three suppliers are not of very high quality and when used for experiment may affect the results of the study.